2021
DOI: 10.3390/jrfm14080338
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Knowledge, Perceived Risk, and Information Search when Purchasing a Franchise: A Comparative Exploration from Australia

Abstract: Franchising has long been a method by which organizations seek to expand and facilitate local market development. However, franchising as a growth strategy can often be hampered by lack of suitable franchisees. To mitigate this shortage, some franchisors have engaged in recruiting franchisees internally from the ranks of their employees in addition to the traditional approach of recruiting franchisees externally. Predominantly franchisees are individuals rather than corporations and thus purchasing a franchise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Research has shown that subjective knowledge impacts many variables, such as perceived risk (Rahmafitria et al, 2021) and travel intention (Tassiello & Tillotson, 2020) and is also critical in predicting consumers' decision‐making behaviors (Balsarini et al, 2021). For instance, Phillips et al's (2013) study supported a positive impact of the US upper Midwesterners' subjective knowledge of Korean food on their attitude toward consuming the product, which further predicted their intention to travel to Korea.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research has shown that subjective knowledge impacts many variables, such as perceived risk (Rahmafitria et al, 2021) and travel intention (Tassiello & Tillotson, 2020) and is also critical in predicting consumers' decision‐making behaviors (Balsarini et al, 2021). For instance, Phillips et al's (2013) study supported a positive impact of the US upper Midwesterners' subjective knowledge of Korean food on their attitude toward consuming the product, which further predicted their intention to travel to Korea.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indeed, it is the rich human capital provided by their various backgrounds, skills and accumulated knowledge that makes franchisees so attractive from a resource scarcity viewpoint (Norton 1988b). This research categorizes franchisees into the distinct dyads of internally recruited franchisees who, before becoming franchisees, were employees of the franchisor, and externally recruited franchisees who have come from outside the franchise system (Balsarini et al 2021). Until recently, the internal recruitment of franchisees had effectively been ignored in the literature (Balsarini et al 2022), despite being a well-established industry practice representing approximately 40% of franchisees, the remaining 60% being externally recruited (Lashley and Morrison 2000).…”
Section: Franchisee Provenance-the Business Diversity Provided By Fra...mentioning
confidence: 99%